GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 117704 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false Geometry: POLYGON((-72.333984 8.298470,-71.542968 8.906780,-70.290527 9.752370,-68.642578 10.314919,-68.203125 10.163560,-69.104003 9.600749,-70.180664 8.537565,-70.971679 7.863381,-71.389160 7.057282,-72.224121 7.144498,-72.707519 7.732765,-72.333984 8.298470)). The dataset includes 117704 records from 225 constituent datasets: 1 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 240 records from International Barcode of Life project (iBOL). 732 records from A global database for the distributions of crop wild relatives. 4 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 14 records from Phanerogamic Botanical Collections (S). 10 records from MVZ Herp Collection (Arctos). 13 records from University of Vienna, Institute for Botany - Herbarium WU. 7 records from Colección de Entomología - Diptera - Ceratopogonidae. 5 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 1 records from MVZ Mammal Collection (Arctos). 3 records from Coleção de Aves do Museu Nacional / UFRJ. 341 records from LACM Entomology Collection. 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 28 records from Bee Biology and Systematics Laboratory. 228 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 355 records from AntWeb. 59 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2225 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from TCWC Marine Invertebrates. 40 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 7 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 8 records from PRECIS. 40 records from Herbario Nacional Colombiano (COL). 74 records from Fishbase. 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 10 records from Occurrence records of southern African aquatic biodiversity. 2 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 36 records from KUBI Mammalogy Collection. 1 records from UFP - Herbário UFP - Geraldo Mariz. 17 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 48 records from University of Amsterdam (NL) - Páramo pollen reference collection. 130 records from Colección Herbario Federico Medem Bogotá - FMB. 7 records from Herbario Pontificia Universidad Javeriana. 4 records from ICN - Herbário do Instituto de Ciências Naturais. 33 records from Herbario Universidad de Antioquia (HUA). 193 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 1 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 15 records from Lyman Entomological Museum (LEMQ). 1 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 58 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 2 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from Museu Paraense Emilio Goeldi Herbarium. 614 records from CUMV Fish Collection (Arctos). 5 records from Field Museum of Natural History (Zoology) Bird Collection. 2 records from MBM - Herbário do Museu Botânico Municipal. 264 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 27 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Herbario Museo de La Salle Bogotá (MLS). 32 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 324 records from Field Museum of Natural History (Zoology) Mammal Collection. 268 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 21 records from MBML-Aves - Coleção de Aves MBML. 4 records from Tallinn Botanic Garden. 206 records from Museum of Comparative Zoology, Harvard University. 204 records from Australia's Virtual Herbarium. 40 records from Ichthyology Collection - Royal Ontario Museum. 3 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 50974 records from EOD - eBird Observation Dataset. 28 records from iNaturalist Research-grade Observations. 6 records from UCBG TAPIR Provider. 1 records from Global caridean shrimp fauna. 151 records from CONN. 105 records from Recent Invertebrates Specimens. 65 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 25 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 10 records from University of California Museum of Paleontology. 43 records from Mammals housed at MHNG, Geneva. 4 records from Estonian University of Life Sciences. 160 records from CAS Ichthyology (ICH). 29 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 8 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 19 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 503 records from TNHC Ichthyology Collection. 34 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Colección de Entomología - Auchenorrhyncha. 1 records from Bryophyte herbarium, NTNU University Museum. 12 records from Illinois Natural History Survey Insect Collection. 181 records from naturgucker. 7 records from Cleveland Museum of Natural History.. 16 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 34 records from UMMZ Mammal Collection. 1 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 8 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 15 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 28 records from Registros biológicos del género Piper en el herbario HUA. 3 records from SBMNH Vertebrate Zoology. 4 records from Colección de Entomología - Curculionidae. 88 records from CM Herps Collection. 6 records from UEC - Herbário da Universidade Estadual de Campinas. 8 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 2 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 13 records from Lichen herbarium, Oslo (O). 45 records from ICN - Universidad Nacional de Colombia. 65 records from LACM Vertebrate Collection. 1 records from Collection Crustacea - ZMB. 10 records from The Fungal Collection at the Botanische Staatssammlung München. 71 records from The Lichen Collection at the Botanische Staatssammlung München. 74 records from Universidad Autónoma de Madrid, Biología, Acalypha. 16069 records from Tropicos Specimen Data. 239 records from Natural History Museum (London) Collection Specimens. 20 records from Natural History Museum, Vienna - Herbarium W. 1231 records from Macaulay Library Audio and Video Collection. 6 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 3 records from Harold W. Manter Laboratory of Parasitology Collection. 5 records from Field Museum of Natural History (Botany) Fungi Collection. 8207 records from NMNH Extant Specimen and Observation Records. 42 records from ANTARCTIC PLANT DATABASE. 2 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 2 records from Canadian Museum of Nature Herbarium. 51 records from UF Florida Museum of Natural History Mammals. 34 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 10 records from The AAU Herbarium Database. 18 records from Real Jardin Botanico, Madrid: MA-Musci. 63 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 3 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 1 records from Michigan State University Herbarium Lichens. 1 records from LSUMZ Mammals Collection. 740 records from Paleobiology Database. 87 records from herbario. 255 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 50 records from Arizona State University Amphibian and Reptile Collection. 248 records from Arizona State University Lichen Collection. 47 records from DAV UC Davis Center for Plant Diversity. 2 records from Herbarium (UNA). 36 records from MEXU/Plantas Vasculares. 2 records from MEXU/Tipos de plantas vasculares. 6 records from MEXU/Colección de Briofitas. 77 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 3 records from TTU Mammals Collection. 2 records from Herbarium Berolinense. 138 records from Lichen Herbarium Berlin. 42 records from Biologiezentrum Linz. 18 records from United States National Plant Germplasm System Collection. 398 records from The System-wide Information Network for Genetic Resources (SINGER). 16 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 156 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 73 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 3 records from Harvard University Herbaria. 1 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 138 records from MAL. 29 records from Naturalis Biodiversity Center (NL) - Aves. 9 records from Mosquito Occurrence Dataset. 5 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 1 records from UCM Bird Collection (Arctos). 5 records from UCM Amphibian and Reptile Collection (Arctos). 1 records from CNIN/Coleoptera. 14 records from Colorado Plateau Museum of Arthropod Biodiversity. 1 records from USF Herbarium. 42 records from MLZ Bird Collection (Arctos). 2 records from Herbarium of Umeå University (UME). 229 records from Field Museum of Natural History (Botany) Seed Plant Collection. 11 records from MPM Milwaukee Public Museum Herbarium. 4 records from Sand flies of Eastern Africa. 298 records from Coleccion de sonidos ambientales. 1657 records from Texas A&M University Insect Collection. 6 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 4 records from Collection Arachnology SMF. 34 records from Herbarium Senckenbergianum (FR). 2 records from Collection Aves (bird skins) SMF. 201 records from SINGER Coordinator. 1 records from MEXU/Leguminosae. 14 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 8 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 1 records from Códigos de barras de ADN del marcador COI de aves y tejidos de la colección del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. 9 records from UPCB - Herbário do Departamento de Botânica. 1 records from Collection ornithologique A. Maës. 3 records from Queensland Museum provider for OZCAM. 13 records from CUMV Amphibian Collection (Arctos). 2 records from NMSA: Arthropod Collections (1900-2012). 80 records from Lund Botanical Museum (LD). 20020 records from Snow Entomological Museum Collection. 26 records from Geographically tagged INSDC sequences. 2 records from Field Museum of Natural History (Zoology) Fish Collection. 1 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 30 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from University of Tennessee at Chattanooga. 1 records from Bernice P. Bishop Museum. 1 records from CUMV Reptile Collection (Arctos). 1 records from Carnet en Ligne. 36 records from Colección del Herbario PSO de la Universidad de Nariño. 52 records from UMMZ Birds Collection. 1 records from Australian National Insect Collection. 36 records from Royal Botanic Garden Edinburgh Herbarium (E). 3 records from Colección de Entomología - Coleoptera. 5 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 9 records from Botany (UPS). 88 records from Instituto de Ciencias Naturales. 3 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 92 records from Mammalogy Collection - Royal Ontario Museum. 4 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 1 records from JPB - Herbário Lauro Pires Xavier. 3451 records from Insect Occurrence Data from MIZA. 1 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 2 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 41 records from Herbario de la Universidad Industrial de Santander. 157 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 44 records from CAS Herpetology (HERP). 2 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 1166 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 7 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 1 records from Hymenoptera. 218 records from AUM Fish Collection. 39 records from Global compendium of Aedes aegypti occurrence. 2 records from NCSM Invertebrates Collection. 3 records from UB - Herbário da Universidade de Brasília. 17 records from Colección de Entomología - Orthoptera. 81 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 25 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 20 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 3 records from Fiocruz/CLIOC - Coleção de Leishmania. 6 records from Registros Primates Neotropicales Convocatoria APC. 15 records from MVZ Bird Collection (Arctos). 2 records from KUBI Ornithology Collection. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 116 records from UF FLMNH Ichthyology. 1 records from New Zealand Fungal and Plant Disease Collection (PDD). 1 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 21 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 284 records from Geneva Herbarium – General Collection (G). 71 records from Instituto de Botánica Darwinion. 125 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 251 records from CAS Botany (BOT). 1 records from South Australian Museum Australia provider for OZCAM. 2 records from Lichen herbarium, UiB. 1 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences